2011
DOI: 10.1089/acm.2010.0687
|View full text |Cite
|
Sign up to set email alerts
|

Earthing the Human Body Influences Physiologic Processes

Abstract: Earthing the human body influences human physiologic processes. This influence is observed during night relaxation and during physical activity. Effect of the earthing on calcium-phosphate homeostasis is the opposite of that which occurs in states of weightlessness. It also increases the activity of catabolic processes. It may be the primary factor regulating endocrine and nervous systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 8 publications
1
25
0
1
Order By: Relevance
“…In particular, Marino et al [1974] and Harutyunyan and Artsruni [2013] reported changes in serum protein fractions of rats exposed to vertical fields of 0.6-19.7 kV/m and 200 kV/m. These results were consistent with data provided by Sokal and Sokal [2011], who showed increased content of alfa1-and alfa-2 globulin fractions in serum of humans grounded for 7 days. In our experiments, the mentioned fractions were diminished in ESF-exposed rats.…”
Section: Introductionsupporting
confidence: 93%
“…In particular, Marino et al [1974] and Harutyunyan and Artsruni [2013] reported changes in serum protein fractions of rats exposed to vertical fields of 0.6-19.7 kV/m and 200 kV/m. These results were consistent with data provided by Sokal and Sokal [2011], who showed increased content of alfa1-and alfa-2 globulin fractions in serum of humans grounded for 7 days. In our experiments, the mentioned fractions were diminished in ESF-exposed rats.…”
Section: Introductionsupporting
confidence: 93%
“…It has been reported that electrons in the body neutralize reactive oxygen species, which help the body's immune and inflammatory responses . Therefore, the presence of these positive static charges on the skin surface is a major problem affecting the feeling, appearance, and health of skin . Through direct contact or through animal skins used as footwear or sleeping mats, the ground's abundant free electrons can enter the body, which is electrically conductive .…”
Section: Transferred Charge Density On Skin By Friction With Ptfe Nymentioning
confidence: 99%
“…Seven-hour earthing of an insulated human body causes a decrease in serum concentrations of total protein and albumin, while it increases the concentration of globulins. However 1-hour interruption of human contact with the earth causes an increase in total protein and globulin concentrations [4]. …”
Section: Introductionmentioning
confidence: 99%